Markers of Hemostatic System Activation in Acute Deep Venous Thrombosis-Evolution during the First Days of Heparin Treatment - The DVTENOX Study Group (Thrombosis and Haemostasis, 1993)
Fibrin D-Dimer (D-Di), prothrombin activation fragment (F 1+2) and thrombin-antithrombin III complexes (TAT) were measured using ELISA procedures in the plasma of patients with an acute deep venous thrombosis (DVT), at presentation and on days 2, 6 and 10 after initiation of heparin treatment. Patients were randomly allocated into two treatment groups: 44 patients received adapted doses of continuous intravenous unfractionated heparin (UH) whereas 47 received 1 mg/kg every twelve hours of a low molecular weight heparin (enoxaparin) subcutaneously. A phlebography and a perfusion lung scan were performed before inclusion and on day 10. Failure of therapy (n = 9) was defined by venogram worsening or confirmed pulmonary embolism. Improvement (n = 44) or stationary state (n = 38) were defined by venogram evolution in the absence of new leg scan defects.At presentation, D-Di, F 1 + 2 and TAT were above cut-off values in 97, 66 and 89% of patients respectively. D-Di levels correlated with the extent of venous thrombosis whereas TAT and F 1 + 2 did not. Mean levels of D-Di decreased sharply during the first days of treatment but were still abnormal on day 10. A secondary increase of D-Di on days 6 or 10 by more than 3 μg/ml occurred in 4 of the 9 patients who developed a thromboembolic recurrence but in none of the 72 patients who had a more favorable outcome. F 1 + 2 and TAT time-courses were not related to clinical evolution. In the Enoxaparin group, there was no relationship between antifactor Xa activities and any biological markers. TAT and F 1 + 2 levels fell on day 2 and remained stable until day 10. In contrast, in the UH group, TAT and F 1 + 2 did not significantly decrease on day 2, probably due to a delay in dose adaptation, but they declined slowly until day 10.In conclusion, D-Di displays a higher sensitivity than F 1 + 2 or TAT for the diagnosis of D\T. D-Di, but not TAT or F 1 + 2, follow-up seems to be of potential value for early detection of recurrency. Hemostatic activation is controlled earlier by fixed doses of a low molecular weight heparin, irrespective of the plasma anti-factor Xa activities, than by unfractionated heparin at adapted doses.